Green development through built form and knowledge community environment in science city: a lesson based on the case study of Cyberjaya, Malaysia and Tsukuba Science City, Japan - Rashidi, Mohd. Hisyam (Dr. Hisyam rashidi, 2010)
This paper explains a way and lesson for green development through built form and knowledge community environment in the science city. A science city is known as a place for research and development activities, a science city involves the creation of new settlements, business, recreations, institutions, and cultural activities. this paper addresses place making, built form studies and a knowledge community planning. In addition, this paper emphasizes the comparative physical development between Cyberjaya, Malaysia and tsukuba Science City, Japan describes how people perceive with their living and working environment. The result shows how sustainable development concept anc design approach can be applied through the science city experience. The findings suggested some criteria of physical development such as green setting, built form, place making, and community environment.